Economic policy and the Covid-19 crisis : the macroeconomic response in the US, Europe and East Asia - Andréosso-O'Callaghan, Bernadette, 1959-; Mun, U-sik, 1960-; Son, Uk (New York, NY : Routledge, 2022)
"This book offers an assessment of the different monetary and fiscal policy responses that have been implemented by national governments in major European and Asian countries faced with the Covid-19 crisis since 2020; it also deals with the case of the US experience as a benchmarking example. The book provides a comprehensive cross-country comparative study on health crisis management at the macroeconomic level. Its focus on monetary and fiscal policies across different countries in Asia, Europe and the USA makes it unique. Divided into three parts following a general introduction that sets the context of the study, the book deals with the case of the USA, EU and European countries as well as with that of key Asian countries. Of specific relevance is the European Union and euro-area contexts that serve as a framework to the different EU national monetary and fiscal policy responses. Each chapter deals with a specific country, including Italy and the UK in Europe and Singapore and South Korea in Asia, and covers the following topics: the extent of the outbreak of the public health crisis and its macroeconomic impact; the comparative examination of fiscal and monetary policy responses to both crises; and an overall assessment of the effectiveness of these policies along with the public health policy to mitigate the economic impact. Given the unprecedented nature of the Covid-19 crisis, anyone eager to know more about its macroeconomic impact and ensuing policies in a comparative framework will be keen to read this book. It will be essential reading to any researcher, policy maker and/or analyst working in the area of public policy and is also a unique contribution to the field of European studies, Asian studies and Comparative Economic Studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Economic policy -- Case studies; Fiscal policy -- Case studies; Monetary policy -- Case studies; COVID-19 (Disease) -- Economic aspects -- Case studies; BUSINESS & ECONOMICS / Money & Monetary Policy; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / International / Economics